The influence of menstrual cycle on metabolic control and diet in patients with phenylketonuria - Laura Horka; Kristin Landolt; Zoran Erlic; Nicole Rimann; Alessio Cremonesi; Michel Hochuli; Felix Beuschlein (Orphanet Journal of Rare Diseases)
Abstract Based on experiences from everyday clinical practice and indications from the literature, the menstrual cycle might impact on metabolic stability in patients with urea cycle disorders and organic acidurias. However, this connection has not yet been systematically investigated. Phenylketonuria (PKU) as the most prevalent inborn error of metabolism with its easily determinable biomarker is a suitable model disease to shed light on this question. In ten patients with classic PKU on a low protein diet and on an amino acid mixture, phenylalanine (Phe) was measured from dried blood spots twice a week for 6 months. During this time, the patients documented their menstrual cycle and filled in nutrition protocols since it is known that the menstrual cycle also influences nutritional behavior. Based on this cohort, we found a significant correlation between the phases of the menstrual cycle and Phe concentration, with the lowest concentrations in the early luteal phase and the highest in the early follicular phase, during menstrual bleeding. This effect did not appear to be due to a change in eating behavior, as both protein and calorie intake were not significantly different in relation to the menstrual cycle. Since the increase in Phe began before menstrual bleeding, it does also not appear to be a pure effect of catabolism due to bleeding. Further studies will be required to identify the cause of this effect and to develop possible therapeutic strategies.